Implementasi ajaran Tamansiswa TRI N sebagai pendidikan karakter pembiasaan cuci tangan di SD Negeri 2 Padokan - Haryono , Angelina Nazalina; Indriyanti, Poppy (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to implement the teaching of Tamansiswa “Tri N” in cultivating character education at SDN 2 Padokan. Observations from the research results show that students have implemented the habit of washung their hands before and after eating. Students are taught by teachers about the importance of washing their hands before and after eating. This research is a qualitative descriptive study that describe the implementation of “Tri N” through hand washing activities for students at SDN 2 Padokan. The object of this research was carried out at the hand washing place at SDN 2 Padokan and carried out before and after washing. Data collection techniques used include observation and interview techniques. Instiling character education maintaining cleanliness by applying the “Tri N” principles in hand washing activities can be carried out well. This is reflected in the teacher`s ability to teach students the hand washing habits so that they can imitate this positive habit.